Alternation of histone and DNA methylation in human atherosclerotic carotid plaques - Greißel, Anna; Culmes, Mihaela; Napieralski, Rudolf; Wagner, Ernst; Gebhard, Harry; Schmitt, Manfred; Zimmermann, Alexander; Eckstein, Hans-Henning; Zernecke, Alma; Pelisek, Jaroslav (Thrombosis and Haemostasis, 2015)
Little is known about epigenetics and its possible role in atherosclerosis. We here analysed histone and DNA methylation and the expression of corresponding methyltransferases in early and advanced human atherosclerotic carotid lesions in comparison to healthy carotid arteries. Western Blotting was performed on carotid plaques from our biobank with early (n=60) or advanced (n=60) stages of atherosclerosis and healthy carotid arteries (n=12) to analyse di-methylation patterns of histone H3 at positions K4, K9 and K27. In atherosclerotic lesions, di-methylation of H3K4 was unaltered and that of H3K9 and H3K27 significantly decreased compared to control arteries. Immunohistochemistry revealed an increased appearance of di-methylated H3K4 in smooth muscle cells (SMCs), a decreased expression of di-methylated H3K9 in SMCs and inflammatory cells, and reduced di-methylated H3K27 in inflammatory cells in advanced versus early atherosclerosis. Expression of corresponding histone methyltransferases MLL2 and G9a was increased in advanced versus early atherosclerosis. Genomic DNA hypomethylation, as determined by PCR for methylated LINE1 and SAT-alpha, was observed in early and advanced plaques compared to control arteries and in cell-free serum of patients with high-grade carotid stenosis compared to healthy volunteers. In contrast, no differences in DNA methylation were observed in blood cells. Expression of DNA-methyltransferase DNMT1 was reduced in atherosclerotic plaques versus controls, DNMT3A was undetectable, and DNMT3B not altered. DNA-demethylase TET1 was increased in atherosclerosisc plaques. The extent of histone and DNA methylation and expression of some corresponding methyltransferases are significantly altered in atherosclerosis, suggesting a possible contribution of epigenetics in disease development.
Keywords: Carotid artery; atherosclerosis; epigenetics; DNA and histone methylation; methyltransferases